Prevalence of Neck Pain in Drivers - Rana Abdul Wahab, Sadia Khalid, Fatima Khalid, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Neck pain is a common problem. About two-thirds of people will experience neck pain at some point in their lives. People in general, and drivers in particular, often have neck pain that doesn't go away. Neck pain is a common cause of disability, but not much is known about how often it happens or how it acts. Objective: The goal of this study was to find out how many drivers have neck pain. Methodology: A cross-sectional study was done, and the data were gathered through convenient sampling. From different taxi stands in Lahore, Pakistan, 150 people filled out self-reported questionnaires to gather data. The SPSS20.0 software was used to analyze the data that was collected, and the results were figured out. Results: We can say that physical work, driving, and sitting in a chair are the main things that can make neck pain worse or better. The Visual Analogue Scale is used to measure how often and how bad neck pain is caused by driving (VAS). We found that 65 percent of the people who answered the survey have neck pain. 42 of the 150 people who answered said they had mild pain. The other 39 people who answered said they had average pain while driving, and only 17 of the 150 people who answered said they had high pain. On the other hand, Neck Disability Index NDI checked the pain level for physical work and sitting in a chair. Also, "during physical work and sitting on chair" are two things that have more to do with how bad the neck pain is because these two things also make it worse for drivers to have neck pain. Keywords: Prevalence of Neck Pain, Physical Work, Sitting on Chair, Driving.